Analisis Kekuatan Alat Bukti Pembukuan Perusahaan Dalam Hukum Positif Dan Hukum Islam - Muslih, Muslih (STAI Al-Mas'udiyah, 2023)
The rise of companies in Indonesia has led to various kinds of competition, so that if it is not controlled, it is feared that it will lead to unfair (fraudulent) business competition. As for the formulation of the problem in this paper, the first is the definition of evidence in general and the company's bookkeeping evidence, the second is how the strength of the company's bookkeeping evidence is in positive law and Islamic law. The type of research in writing this law is normative legal research or library research, namely legal research by examining library materials or secondary data consisting of primary legal materials. The results of this study the authors conclude with the enactment of provisions governing company documents, the creation, storage, transfer, destruction and submission of company documents can be carried out simply, effectively and efficiently without reducing legal certainty and still protecting the interests of the parties in a legal relationship . Provisions regarding the implementation of storage, transfer, destruction and delivery of documents regulated by this Law are not intended to eliminate the function of the documents concerned as evidence or other legal interests. Keywords;Evidence, Bookkeeping